How efficient is exemplary teaching in learning equations and inequations in the third and fourth grade of primary school? - Malinović-Jovanović Nela T.; Simić Milica D.; Ristić Milica N. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
The aim of the study was to investigate the efficiency of learning equations and inequations through the application of exemplary teaching in primary school. In terms of efficiency and achievement levels, we started from the learning outcomes on equations and inequations taught in the third and fourth grade primary school mathematics curriculum and from a taxonomic model of operationalization of the goals and objectives of mathematics teaching in the cognitive domain. According to this model, the performance of the students was examined in the following 5 main taxonomy levels: recognition, reproduction, comprehension, operationalization and creative problem solving. The results of the experimental study, which was carried out on a sample of 100 students, show that the teaching method used helps students to learn equations and inequations more successfully. The use of exemplary teaching had a positive effect on students' performance in reproduction, comprehension, operationalization, and creative problem solving, while it had no effect on students whose knowledge was at the recognition level. The results of this study could lead to changes in the presentation of the teaching content, the evaluation of the efficiency of the educational process, a more efficient individualization of the learning process, etc. In addition, the methodological contribution of this work is the creation of exemplary teaching models whose use in a classroom, thanks to analogue reasoning, allows students to find their own approach to mathematics.